Effect of cut tobacco size and distribution on critical cigarette quality characteristics of "slim cigarette" processing technology. Issue 6 (January 2021) - Zou, Quan; Zhang, Tao; Zhao, Yunchuan; Chen, Ran; Yang, Lei; Hu, Qun; Wu, Jia Can; Xu, Yan Qun; Pu, Qian; Zhao, Mei Wei; Qiu, Ye; Feng, Hongtao
Abstract: To further improve the stability of quality control on the processing technology of slim cigarettes in the process of cigarette manufacturing. In this study, based on the blending formula of product A, the cut tobacco screened out by different sieves was rolled according to different proportions. The cigarette structure, physical properties, tobacco loss from cigarette-end, dust content, and density of tobacco rod were systematically evaluated. The results showed that the proportion of medium and short cut tobacco (1.0 mm ∼ 3.35 mm) ≥ 62%, and the whole cut tobacco ratio in the cigarette was less than 40%, which could effectively improve the fluctuation of slim cigarette physical properties and the distribution stability of cut tobacco in tobacco rod.